STUDENTS’ NUMERACY THROUGH COMPUTATIONAL THINKING-BASED DIGITAL WORKSHEETS WITH PALEMBANG LOCAL WISDOM CONTEXT - Rosyada, Amrina; Mulyono, Budi; Hapizah, Hapizah (JME (Journal of Mathematics Education), 2025)
This research is motivated by the persistent low level of students’ numeracy skills in Indonesian secondary education. Several pedagogical approaches that may enhance students’ numeracy include the use of digital worksheets, integration of Computational Thinking (CT), and incorporation of Palembang local wisdom as contextual learning elements. This research aims to describe students’ numeracy skills through the use of CT-based digital worksheets with Palembang local wisdom context, an approach not previously explored in existing studies. This research employed a descriptive method using a qualitative approach. The research participants were 34 tenth-grade students at MAN 2 Palembang, while the research sample consisted of three students representing high, moderate, and low numeracy skills. Data collection techniques included pretest, posttest, and interviews. The results indicate clear variation across ability levels, with distinct differences in numeracy indicators interpreting analysis results to predict and make decisions. High-skill students demonstrated mastery of all numeracy indicators. In contrast, moderate- and low-skill students showed partial or minimal indicator achievement, particularly in interpreting results and constructing conclusions. The study implies that CT-based digital worksheets embedded with Palembang local wisdom contexts can support students’ numeracy skill.